EVALUATION OF RADICAL CHOLECYSTECTOMY FOR INCIDENTAL GALLBLADDER CARCINOMA DIAGNOSED AFTER CHOLECYSTECTOMY, SINGLE CENTER EXPERIENCE - Kamran Safdar (Army Medical College Rawalpindi, 2021)
Objective: To evaluate the procedure of radical cholecystectomy for incidental gallbladder carcinoma diagnosed after cholecystectomy at a tertiary care teaching hospital of Pakistan.